Redescription of a wall crab spider species from Taiwan: Siamspinops formosensis (Kayashima, 1943) comb. nov., with the first description of males and taxonomic notes (Araneae: Selenopidae) - Yu, Kuang-Ping; Lo, Ying-Yuan; Huang, Wen-Chun; Hsiao, Yun; Ding, Tzung-Su (Zootaxa, 2019)
The wall crab spider Selenops formosensis Kayashima, 1943 was described from three females collected from northern Taiwan (Kayashima 1943a), but subsequently referred to as S. formosanus and S. formosansis in an illustrated handbook on Taiwanese spiders written by the same author (Kayashima 1943b). The original descriptions lacked illustrations of the epigyne or vulva which are extremely useful in determining genera and species of Selenopidae.